Qualification of Copyright as Joint Property Obtained from the Copyrighted Works of Virgoun Songs (Study of Decision No. 1622/PDT.G/2023/PA.JB): Kualifikasi Hak Cipta Sebagai Harta Bersama Yang Diperoleh Dari Karya Cipta Lagu Virgoun (Studi Putusan No. 1622/PDT.G/2023/PA.JB) - Qurniawan, Nafirdo Ricky; Fokky Fuad; Sadino (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Intellectual Property Rights as common property must be shared in principle When a divorce occurs, both in a cumulative lawsuit or a stand-alone lawsuit, but in practice it is not well understood or known in judicial practice in Indonesia, and even still seems foreign. In fact, referring to Article 35 of Law Number 1 of 1974 stipulates that every property acquired during the marriage period is common property, including Intellectual Property Rights, because it is a material right of a part of intangible objects. In the research, the author uses the normative law research method. The issues described were regarding the Judge's Consideration in the West Jakarta District Court Decision No. 1622/Pdt.G/2923/Pa.Jb and discussed the copyright qualification for Virgoun's song as joint property in marriage. From the results of the research, the judge's consideration in the West Jakarta District Court Decision No. 1622/Pdt.G/2923/Pa.Jb is appropriate because in its consideration the Panel of Judges uses reference to the relevant laws and regulations and the Copyright of the Virgoun Song can be legalized as Joint Property in Marriage based on Article 35 paragraph (1) of the Marriage Law.